Generation and characterization of mice carrying a conditional allele of the Wwox tumor suppressor gene. - John H Ludes-Meyers; Hyunsuk Kil; Jan Parker-Thornburg; Donna F Kusewitt; Mark T Bedford; C Marcelo Aldaz (PLoS ONE)
WWOX, the gene that spans the second most common human chromosomal fragile site, FRA16D, is inactivated in multiple human cancers and behaves as a suppressor of tumor growth. Since we are interested in understanding WWOX function in both normal and cancer tissues we generated mice harboring a conditional Wwox allele by flanking Exon 1 of the Wwox gene with LoxP sites. Wwox knockout (KO) mice were developed by breeding with transgenic mice carrying the Cre-recombinase gene under the control of the adenovirus EIIA promoter. We found that Wwox KO mice suffered from severe metabolic defect(s) resulting in growth retardation and all mice died by 3 wk of age. All Wwox KO mice displayed significant hypocapnia suggesting a state of metabolic acidosis. This finding and the known high expression of Wwox in kidney tubules suggest a role for Wwox in acid/base balance. Importantly, Wwox KO mice displayed histopathological and hematological signs of impaired hematopoiesis, leukopenia, and splenic atrophy. Impaired hematopoiesis can also be a contributing factor to metabolic acidosis and death. Hypoglycemia and hypocalcemia was also observed affecting the KO mice. In addition, bone metabolic defects were evident in Wwox KO mice. Bones were smaller and thinner having reduced bone volume as a consequence of a defect in mineralization. No evidence of spontaneous neoplasia was observed in Wwox KO mice. We have generated a new mouse model to inactivate the Wwox tumor suppressor gene conditionally. This will greatly facilitate the functional analysis of Wwox in adult mice and will allow investigating neoplastic transformation in specific target tissues.